2018
DOI: 10.1088/1361-6463/aab631
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced infrared transmission through subwavelength hole arrays in a thin gold film mounted with dielectric micro-domes

Abstract: Dielectric micro-domes were mounted on the subwavelength holes of a periodically perforated gold film such that a lens-like micro-dome covers each hole. In comparison to the extraordinary transmission through an array of bare holes in the gold film, this structure showed a further enhanced transmission over a larger range of incident angles with much larger bandwidth at mid-wave infrared wavelengths (m). The structure was fabricated using laser interference lithography, a novel back-exposure with an ultra-viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In case of TE polarization, magnitude of electric remains constant so there is only slight variation in the magnitude of deeps and peaks in the reflectance spectra at different incident angles. In case of TM polarization, magnitude of electric field changes due to which coupling condition for spoof SPPs changes, and hence there is finite variation in the magnitude of deeps and peaks as well as spectral shift in the resonance [55].…”
Section: Discussionmentioning
confidence: 99%
“…In case of TE polarization, magnitude of electric remains constant so there is only slight variation in the magnitude of deeps and peaks in the reflectance spectra at different incident angles. In case of TM polarization, magnitude of electric field changes due to which coupling condition for spoof SPPs changes, and hence there is finite variation in the magnitude of deeps and peaks as well as spectral shift in the resonance [55].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, intensive research has been carried out on coatings of metal and/or dielectric particles as an alternative to continuous antireflection films 5 9 . Their action is based on the excitation of plasmonic 10 , 11 or electromagnetic (EM) resonances 12 15 in metal and dielectric particles, respectively. Compared to continuous films, the capabilities of antireflection coatings made of particles are wider.…”
Section: Introductionmentioning
confidence: 99%
“…This effect can be enhanced by means of the Rayleigh anomaly introducing a diffraction effect occurring owing to the EM radiation scattering on the hole edges [6]- [8]. It was shown that the placement of dielectric particles into metal film holes can give an additional positive effect based on the excitation of magnetic and electrical resonances in dielectric particles [2], [4], [9]- [11]. Although the use of such hybrid metal-dielectric antireflection coatings provides a significant increase in the efficiency of optoelectronic converters in the mid-IR region, they have the disadvantage of containing metal components that cause the dissipation of EM radiation.…”
Section: Introductionmentioning
confidence: 99%